2019
DOI: 10.3390/pharmaceutics12010003
|View full text |Cite
|
Sign up to set email alerts
|

Fab-Arm Exchange Combined with Selective Protein A Purification Results in a Platform for Rapid Preparation of Monovalent Bispecific Antibodies Directly from Culture Media

Abstract: Bispecific antibody (bsAb) applications have exponentially expanded with the advent of molecular engineering strategies that have addressed many of the initial challenges, including improper light chain pairing, heterodimer purity, aggregation, and pharmacokinetics. However, the lack of high-throughput methods for the generation of monovalent bsAbs has resulted in a bottleneck that has hampered their therapeutic evaluation, as current technologies can be cost-prohibitive and impractical. To address this issue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The method used here to make bsAbs (cFAE) allows for rapid generation of human IgG1-like bsAbs from any antibody pair and is applicable to larger scale manufacturing 50 , making it a straightforward way to rapidly deploy new bsAb candidates to combat the pandemic. The method could eventually be further simplified, as it was shown that the cFAE reaction can happen by adding reducing agent directly to the supernatant, before protein harvesting, which would eliminate the additional step of purifying 2 antibodies separately before getting the desired bsAb product 59 Besides the Fab specificity, it is important for engineered therapeutic IgGs to retain their Fc effector functions for optimal in vivo efficacy. We demonstrated comparable levels of ADCP and ADCT for the bsAbs and their parental counterparts, as well as retained neutralization following introduction of Fc mutations necessary for the formation of bsAbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used here to make bsAbs (cFAE) allows for rapid generation of human IgG1-like bsAbs from any antibody pair and is applicable to larger scale manufacturing 50 , making it a straightforward way to rapidly deploy new bsAb candidates to combat the pandemic. The method could eventually be further simplified, as it was shown that the cFAE reaction can happen by adding reducing agent directly to the supernatant, before protein harvesting, which would eliminate the additional step of purifying 2 antibodies separately before getting the desired bsAb product 59 Besides the Fab specificity, it is important for engineered therapeutic IgGs to retain their Fc effector functions for optimal in vivo efficacy. We demonstrated comparable levels of ADCP and ADCT for the bsAbs and their parental counterparts, as well as retained neutralization following introduction of Fc mutations necessary for the formation of bsAbs.…”
Section: Discussionmentioning
confidence: 99%
“…The method used here to make bsAbs (cFAE) allows for rapid generation of human IgG1-like bsAbs from any antibody pair and is applicable to larger scale manufacturing 50 , making it a straightforward way to rapidly deploy new bsAb candidates to combat the pandemic. The method could eventually be further simplified, as it was shown that the cFAE reaction can happen by adding reducing agent directly to the supernatant, before protein harvesting, which would eliminate the additional step of purifying 2 antibodies separately before getting the desired bsAb product 59…”
Section: Discussionmentioning
confidence: 99%
“…Associated with that, AstraZeneca recently published a method for high throughput bispecific antibody screening, applying matched F405L and K40R mutations [34]. In addition, H435R and Y436F (also known as RF-mutation) were incorporated into one of the CH 3 mutants (K409R).…”
Section: Controlled Fab-arm Exchange ("Duobodies")mentioning
confidence: 99%
“…All six resulting bispecific antibodies could be produced with high heterodimer purity as demonstrated by liquid chromatography-mass spectrometry (LCMS) and reverse phase liquid chromatography (RPLC) and showed bispecific target engagement proven by BLI. Compared to the conventional DuoBody generation, this approach enables the formation of bispecifics directly from culture-supernatants without any pre-purification steps of monospecific antibodies, making it perfectly suited as a bispecific screening tool [34].…”
Section: Controlled Fab-arm Exchange ("Duobodies")mentioning
confidence: 99%
“…The development of such techniques is therefore important to increase efficiency and reduce cycle times of bispecific therapeutic antibody discovery. Some technologies already exist for the generation and assessment of binder combinations in standard IgG-formats, including Genentechs knob-into-hole based half-antibodies 25 – 27 and Genmabs IgG4 based Fab Arm exchange technologies 28 – 30 and variations thereof 31 , 32 . These approaches may still pose in some aspects technical challenges (dimers or aggregates in half antibody production; high-throughput monitoring of IgG4 exchange efficacies), but overall can be considered as valuable, sufficiently robust, and state-of-the-art technologies for generating binder-binder matrices in a bivalent IgG format.…”
Section: Introductionmentioning
confidence: 99%